Answer:
Explanation:
Hypotenuse: 65
Leg: 25
Let Hypotenuse be c, and leg be a
+
![b^(2) = c^(2)](https://img.qammunity.org/2022/formulas/mathematics/college/q7o18zbw7bxuwvlkjr444ytwj4q1wcigpn.png)
![a^(2) + 25^(2) = 65^(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/lqic0vki81esatiygzwt8gnarikq3jaw5l.png)
![a^(2) + 625 = 4225\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/nkod5y5c0xupe937zx2zurrxi0fhhn9666.png)
= 4225 - 625
= 3600
3600 is the exponential value of a, meaning we need to apply the opposite of squaring to get the value of b. Which is square rooting.
a =
![√(3600\\)](https://img.qammunity.org/2022/formulas/mathematics/high-school/jdg44zszjhn8q4w0u0x34pjhr07fk6cp1a.png)
a = 60
Therefore a is equal to 60 feet